1970
DOI: 10.1037/h0029159
|View full text |Cite
|
Sign up to set email alerts
|

Runway performance in rats as a function of goal-box placements and goal-event sequence.

Abstract: The effects of intertrial reinforcement (ITR), partial delay (PD) of reinforcement, intertrial nonreinforcement (ITN), and the sequence of goal events per se on acquisition and extinction performance were investigated in a series of three runway experiments with rats. With limited training, ITRs following nonreinforced (N) trials attenuated the typically obtained partial reinforcement extinction effect (FREE), whereas when training was extended this procedure failed to eliminate the FREE. The ITRs when adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…McCain (1966, Exp. IV) replicated this finding and further showed that reduced persistence of responding during extinction did not occur when ITRs were given only following R trials. Similar findings have recently been reported by Homzie, Rudy, and Carter (1970).…”
Section: Experiments IIIsupporting
confidence: 93%
“…McCain (1966, Exp. IV) replicated this finding and further showed that reduced persistence of responding during extinction did not occur when ITRs were given only following R trials. Similar findings have recently been reported by Homzie, Rudy, and Carter (1970).…”
Section: Experiments IIIsupporting
confidence: 93%
“…If it is assumed that the reinstatement of S N from placements on the subsequent long-run trial becomes weaker as training progresses, a number of additional findings may be interpreted. It would be expected, for example, that a group which receives nonrewarded placements intermixed with consistently rewarded long runs would be more resistant to extinction early in training than later in training, as has been found by, for example, Homzie et al (1970). Also, it would be expected that if Experiment 1 had employed a limited number of training trials, Group N-Rshort-run and Group N-Rlong-run would be about equal in resistance to extinction and more resistant to extinction than Group R, as has been found by Homzie et al (1970) employing only six placements.…”
Section: Discussionmentioning
confidence: 88%
“…Working within the context of the aftereffects hypothesis, Capaldi and his colleagues (e.g., Capaldi, Hart, & Stanley, 1963) administered intertrial reinforcements (ITRs) after nonreinforced (N) trials which preceded reinforced (R) trials and eliminated the partial reinforcement extinction effect (FREE). There is evidence (e.g., Homzie, Rudy, & Carter, 1970) that the ITR procedure, while effectively eliminating increased resistance to extinction (Rn) after a few baited goal-box placements, fails to eliminate the FREE after many placements. It has been suggested (e.g., Black & Spence, 1965) that with extended training, generalization between ITR events and runway trials is reduced such that the placement procedure is ineffective in influencing the extinction performance of the runway response.…”
Section: University Of Virginiamentioning
confidence: 99%